Traffic data collection (proceedings of the conference held at the Institution of Civil Engineers, 5-6 April 1978). (Institution of Civil Engineers, 1978)
Proceedings of a joint conference with the Department of Transport and IEE held on 5-6 April 1978.
'A joint conference between the Department of Transport, the Institution of Electrical Engineers, and the Institution of Civil Engineers' - title page verso.
Keywords: Traffic surveys -- Data processing -- Congresses.; Traffic surveys -- Equipment and supplies -- Congresses.; elektronické knihy; electronic books